1999
DOI: 10.1177/00912709922011827
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Bioequivalence Study: Quantification of Fluoxetine and Norfluoxetine by Liquid Chromatography Coupled to Mass Spectrometry

Abstract: In this study, the authors assessed the bioequivalence of two fluoxetine tablet formulations in 24 healthy volunteers of both sexes who received a single 20 mg dose of each fluoxetine formulation, and a new sensitive method for the quantification of fluoxetine and norfluoxetine in human plasma was developed. The study was conducted using an open, randomized, two-period crossover design with a 4-week washout interval. Plasma samples were obtained over a 672-hour period. Plasma fluoxetine and norfluoxetine conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…The overall pharmacokinetic profiles offluoxetine and norfluoxetine in the present study were very close, and in agreement with the data previously published in the relevant literature [17,18,23]. Additionally, the ranges of individual maximal concentrations [15.0--53.5 ng/ml (f1uoxetine), 14.5-73.7 ng/ml (Prozac)] obtained in the study confirmed the previous finding that the absorption rate of f1uoxetine is highly variable [7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall pharmacokinetic profiles offluoxetine and norfluoxetine in the present study were very close, and in agreement with the data previously published in the relevant literature [17,18,23]. Additionally, the ranges of individual maximal concentrations [15.0--53.5 ng/ml (f1uoxetine), 14.5-73.7 ng/ml (Prozac)] obtained in the study confirmed the previous finding that the absorption rate of f1uoxetine is highly variable [7].…”
Section: Discussionsupporting
confidence: 92%
“…This finding strongly supports the conclusion of Moraes and co-workers [18]that quantifying only the parent drug might satisfy future bioequivalence trials of generic f1uoxetine preparations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analytical techniques employed in the recent years for the estimation of sertraline in human plasma include HPLC, GC with popular detectors or in combination with tandem mass spectrometry (i.e. LC-MS/MS and GC-MS/MS) [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the rate of fluoxetine elimination is fairly slow, with a half-life of 47-72 h [2]. Several analytical methods have been reported for determining the levels of only fluoxetine [3,4] or fluoxetine and its active metabolite, norfluoxetine, in biological fluids for therapeutic drug monitoring [5][6][7] and bioavailability studies [8].…”
Section: Introductionmentioning
confidence: 99%